Analysis of the Influence of Socioeconomic Factors on Local Revenue: An Empirical Study in Metro City (2018–2023) - Berta Pramudita (Indonesian Journal Publisher, 2025)
This study aims to examine the influence of population size, inflation, and poverty rate on the Regional Original Revenue (PAD) of Metro City during the period of 2018–2023. As a primary source of local government financing, PAD plays a vital role in supporting fiscal autonomy and sustainable development. An increase in population is expected to expand the tax and retribution base, while inflation affects price stability and household purchasing power. Conversely, a high poverty rate may limit the community’s capacity to contribute to local revenue. The study employs a quantitative approach using multiple linear regression analysis, with the help of E-Views 13 software to process secondary data obtained from the Central Statistics Agency (BPS) of Metro City. The results of the partial t-test reveal that population size exerts the strongest and most significant positive influence on PAD, followed by inflation, which also shows a significant effect but with more variability in direction. Meanwhile, the poverty rate does not have a statistically significant effect on PAD. The F-test results indicate that all three independent variables collectively have a significant impact on PAD. These findings highlight the importance of optimizing PAD by considering demographic dynamics and inflation control, along with strengthening poverty alleviation efforts to establish a more stable and sustainable local revenue base.